2019
DOI: 10.1111/ppe.12541
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of postnatal rapid growth and maternal factors on early childhood growth trajectories

Abstract: Background A range of postnatal and maternal factors influences childhood obesity, but their relative importance remains unclear. This study aimed to assess the relative impact of postnatal rapid growth and maternal factors on early childhood growth trajectories. Subjects Secondary longitudinal analysis of pooled data from the Melbourne Infant Feeding Activity and Nutrition Trial (InFANT) Program and the InFANT Extend Program (n = 977) was performed. Children's height and weight were collected at birth, 3, 9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…The searches identified 41,301 studies, of which 100 studies met the inclusion criteria (Fig 1; S3 Table). Following exclusion of 21 studies that reported duplicate data (S4 Table), 79 studies remained [2098], with sample sizes ranging from 70 to 100,612 (S5 Table); 67 studies were identified in the original searches [20,3398], and a further 12 studies were identified in the updated searches that reported unique data not already included in the review or meta-analysis [2132] (Fig 1; S5 Table). Of these studies, 56 were prospective, 21 reported national-level data, and the majority ( n = 63) were published since 2010.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The searches identified 41,301 studies, of which 100 studies met the inclusion criteria (Fig 1; S3 Table). Following exclusion of 21 studies that reported duplicate data (S4 Table), 79 studies remained [2098], with sample sizes ranging from 70 to 100,612 (S5 Table); 67 studies were identified in the original searches [20,3398], and a further 12 studies were identified in the updated searches that reported unique data not already included in the review or meta-analysis [2132] (Fig 1; S5 Table). Of these studies, 56 were prospective, 21 reported national-level data, and the majority ( n = 63) were published since 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Additional data were available for associations between categorical maternal BMI and continuous child BMI or z -score for children aged 1 to 9 years, but were not included in the meta-analysis [28,32,33,61,76,82,84,8791] (S12 Table), and for associations between continuous maternal BMI and continuous child BMI or z -score for children aged 1 to 18 years [24,36,60,61,71,75,80,85,86,88,9297] (S13 Table). All except 1 showed a significant association between increasing maternal BMI and increasing child BMI or z -score.…”
Section: Resultsmentioning
confidence: 99%
“…49 The current study has highlighted early accelerated growth in Chinese-born mothers in this sample population. Rapid growth is a significant risk factor for later obesity, 9 therefore, a deeper understanding of the factors influencing growth patterns in these ethnic groups in order to intervene early is required. Longitudinal studies into later childhood and adulthood to track zBMI and related health outcomes long term is also recommended.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of the present study is that z-scores have been used to assess growth in children, which is widely recognized as the best system for analysis and presentation of anthropometric data because of its advantages compared to other methods. Furthermore, given that they are sex-independent, their use permits the evaluation of children’s growth status by combining sex and age groups [ 25 ] and has been widely used in recent studies with similar aims [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%